2020
DOI: 10.1038/s41597-020-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

A global ensemble of ocean wave climate projections from CMIP5-driven models

Abstract: This dataset, produced through the Coordinated Ocean Wave Climate Project (COWCLIP) phase 2, represents the first coordinated multivariate ensemble of 21 st Century global wind-wave climate projections available (henceforth COWCLIP2.0). COWCLIP2.0 comprises general and extreme statistics of significant wave height (H S), mean wave period (T m), and mean wave direction (θ m) computed over time-slices 1979-2004 and 2081-2100, at different frequency resolutions (monthly, seasonally and annually). The full ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Overall, the above analyses indicate that both the simulated spatial distributions and seasonal variations in FIO-ESM v2.0 are broadly consistent with the ERA5 data, including not only the monthly but also the 3-hourly significant wave height data. However, the simulated wave parameters still suffer several biases, especially in the North Atlantic, North Pacific, and tropical Pacific oceans, with an approximately 10% relative difference from the ERA5 data, which is similar to other ocean wave data from COWCLIP 28 .…”
Section: Technical Validationsupporting
confidence: 72%
See 1 more Smart Citation
“…Overall, the above analyses indicate that both the simulated spatial distributions and seasonal variations in FIO-ESM v2.0 are broadly consistent with the ERA5 data, including not only the monthly but also the 3-hourly significant wave height data. However, the simulated wave parameters still suffer several biases, especially in the North Atlantic, North Pacific, and tropical Pacific oceans, with an approximately 10% relative difference from the ERA5 data, which is similar to other ocean wave data from COWCLIP 28 .…”
Section: Technical Validationsupporting
confidence: 72%
“…However, ocean waves are not included in most of the state-of-the-art global climate models, which is the key tool to assess and provide future projections of climate systems. Therefore, as the growing demand to understand the response of the global wave climate to increasing greenhouse gas concentrations, especially through the Coordinated Ocean Wave Climate Project (COWCLIP) 1 , several studies on future ocean wave climate research have provided ocean wave information by using the output of global and regional climate models to force the standalone ocean surface wave model 15 28 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Previous studies (Gulev & Grigorieva, 2006; Shimura et al., 2013) demonstrated that the response of wind waves to the changes in atmospheric circulation is quite complex since it is associated both with the changes in the local conditions and the variations in the characteristics of cyclonic activity. This provides another interesting paradigm for further comparative assessments of wind wave model hindcasts with an obvious perspective for the analysis of multimodel projections of wind waves for the 21st century (Morim et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While numerical modelling provides a 'key-hole' to observe the explicit interactions among defined sets of variables, sensitivity analysis provides a way to understand the role of input variables uncertainties in shoreline predictions. Here, we use the framework proposed by D'Anna et al (2020), who used a variance-based Global Sensitivity Analysis (GSA) (Saltelli et al, 2008;Sobol', 2001) to investigate the relative contributions of the uncertainties affecting input variables to the uncertainties of modelled shoreline predictions, and their evolution in time. The method consists in propagating the input uncertainties through the model obtaining a probabilistic estimate of the shoreline projections, and performing a GSA which decomposes the variance of model results into several contributions, each one associated with an input variable.…”
Section: Global Sensitivity Analysismentioning
confidence: 99%